An assessment of the sea breeze energy potential using small wind turbines in peri-urban coastal areas. Issue 139 (April 2015) - Mazon, Jordi; Rojas, Jose I.; Jou, Jordi; Valle, Aaron; Olmeda, David; Sanchez, Carlos
Abstract: From wind speed data recorded hourly at 2 m high during 18 years (1993–2010) in the Llobregat Delta (15 km south of Barcelona city; northeast of the Iberian Peninsula), wind speed distributions at 10 m high were computed for the whole year and for the sea breeze period (from March 1 to September 30, from 10 to 19 local time). Weibull probability density functions fitted to the distributions were used to assess the wind energy generated by two off-grid small wind turbines: the IT-PE-100 and the HP-600W. Results from FAST and AeroDyn simulation tools were compared with those obtained by applying measured wind speeds to manufacturer power curves. Using manufacturer data, the IT-PE-100 would deliver 132 kW h during the whole year (70 kW h during the sea breeze period). From the simulations, the IT-PE-100 would deliver 155 kW h during the whole year (80 kW h during the sea breeze period). It is concluded that the sea-breeze is an interesting wind energy resource for micro-generation, not only in the Mediterranean basin but in other areas of the world with similar wind regimes, and particularly in peri-urban coastal areas where large-scale wind farms cannot be implemented.